Efeito da usinagem, do ciclo térmico de glazeamento e do condicionamento ácido na resistência flexural de uma cerâmica vítrea - Fraga, Sara (2013)
The aim of this study was to evaluate the effect of hard machining, thermal cycle for glazing and acid etching on the surface roughness and flexural strength of a leucite glass-ceramic. Additionally, it was investigated whether the roughness after machining would be influenced by the machining order and by the pair of burs employed. Six pair of burs were used to produce 144 discs by automated machining, which were divided into groups (n=24): 1) machining (M); 2) machining and heat treatment (MH); 3) machining and acid etching (MA); 4) machining, heat treatment and acid etching (MHA); 5) machining and polishing (MP); 6) machining, polishing and acid etching (MPA). The roughness after each treatment was measured using a contact profilometer. The discs were submitted to a piston-on-three ball flexure test (ISO 6872/2008). Weibull analysis was used to compare the characteristic strength (σ0) and Weibull modulus (m) of the groups. The effect of the treatments, machining order and pair of burs on the surface roughness of the specimens was analyzed. Machining reduced the σ0 when compared to polishing. The polishing protocol was able to eliminate the defects introduced by machining, which was observed by means of scanning electron microscopy. The heat treatment did not alter the roughness, but reduced the σ0 and created amorphous material on the ceramic surface, as shown by the x-ray diffraction. Acid etching increased roughness, without reduce σ0. The Weibull modulus did not differ significantly among the groups, which means that all the treatments resulted in similar defects distribution. Spearman s coefficient (rs) indicated strong and significant correlation between machining order and roughness (rsRa = -0,66; rsRz = -0,73). The roughness after machining differed significantly according to the pair of burs employed (p<0,05). Thus, hard machining and thermal cycle for glaze demonstrated a negative effect on the ceramic strength, as opposed to acid etching, which does not appear to affect the flexural strength of the material. Variability in the roughness data could be expected after machining, since the Ra and Rz values seem to be influenced by the machining order and the pair of burs employed.